Students’ Habits On Watching Movies With English Subtitles - Sri Wahyuningsih; Kharisatul Fitriah (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
The habit of watching movies using English subtitles among students has an impact on students' English skills. This study aims to report the students’ views towards the opportunities of watching English-subtitled movies and the challenges they experienced. Using a qualitative method, the data of this study were garnered through semi-structured interviews with five college students at an Indonesian university. The findings reveal that a number of opportunities were gained by the college students through watching English-subtitled movies including having entertainment in students’ free time, promoting exciting English learning media, and enriching English vocabulary. Meanwhile, the students found challenges in watching English-subtitled movies including unfamiliar vocabulary, new English idioms, and various slang languages. Thus, this study promotes the need for efforts among students to overcome these challenges by gaining insight through a lot of sources like books, the internet, articles, and so on.